2016
DOI: 10.1016/j.jaci.2015.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Thymic stromal lymphopoietin controls prostaglandin D2 generation in patients with aspirin-exacerbated respiratory disease

Abstract: Background Prostaglandin D2 (PGD2) is the dominant cyclooxygenase product of mast cells and is an effector of aspirin-induced respiratory reactions in aspirin-exacerbated respiratory disease (AERD). Objective We evaluated the role of the innate cytokine thymic stromal lymphopoietin (TSLP) acting on mast cells to generate PGD2 and facilitate tissue eosinophilia and nasal polyposis in AERD. Methods Urinary eicosanoids were measured in aspirin-tolerant controls and patients with AERD. Nasal polyp specimens fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
112
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(125 citation statements)
references
References 54 publications
4
112
1
8
Order By: Relevance
“…Buchheitt et al reported that increased nasal symptoms in AERD correlated with peak levels of a PGD2 metabolite which could promote ILC2 recruitment and activation (7). These data also indicate that subjective patient symptoms, particularly naso-ocular symptoms, can be correlated with objective laboratory measurements of reaction intensity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Buchheitt et al reported that increased nasal symptoms in AERD correlated with peak levels of a PGD2 metabolite which could promote ILC2 recruitment and activation (7). These data also indicate that subjective patient symptoms, particularly naso-ocular symptoms, can be correlated with objective laboratory measurements of reaction intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one mechanism by which aspirin desensitization may work is by preventing cells from homing into the tissues (29). PGD2 is increased in mast cells from patients with AERD (7) and high doses of aspirin are able to block both COX-1 and COX-2, which may allow for prevention of high amounts of PGD2. Cahill et al showed that, PGD2 decreases after aspirin desensitization and blood eosinophils actually increase in the blood over time (29), presumably due to loss of the PGD2 gradient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Walford and colleagues reported an overall correlation between the number of eosinophils and ILC2s in nasal polyps but they did not specifically compare ILC2 numbers in AERD versus CRSwNP nasal polyps 50 . Similar to eosinophils, mast cell numbers did not significantly differ between CRSwNP and AERD nasal polyps 41, 52 . However, mast cells are a major source of prostaglandin D2 (PGD 2 ) and this inflammatory mediator has been shown to be significantly elevated in AERD compared to CRSwNP patients, especially after aspirin challenge 52, 53 .…”
Section: Disease Pathophysiologymentioning
confidence: 77%
“…Similar to eosinophils, mast cell numbers did not significantly differ between CRSwNP and AERD nasal polyps 41, 52 . However, mast cells are a major source of prostaglandin D2 (PGD 2 ) and this inflammatory mediator has been shown to be significantly elevated in AERD compared to CRSwNP patients, especially after aspirin challenge 52, 53 . Finally, basophil numbers were significantly reduced in AERD versus CRSwNP nasal polyps 46 .…”
Section: Disease Pathophysiologymentioning
confidence: 77%